Aplikasi Virtual Reality untuk Media Terapi Phobia Ketinggian - Muhamad Akbar Triadi Fadillah; Aldy Putra Aldya; Eka Wahyu Hidayat (Sekawan Institut, 2024)
This research aims to develop a therapy application using Virtual Reality technology and a smartwatch to view heart rate data as an assessment in dealing with and assessing how bad Arcophobia (phobia of heights) is in users. The application built is a Virtual Reality (VR) application on the Android platform and applies the Exposure-Based Therapy (EBT) method, the Exposure-Based Theraphy (EBT) method is a method that applies an introduction to phobias suffered gradually according to the ability of the sufferer, in this case the EBT method is proven effective in reducing phobias including Arcophobia. The use of multimedia elements is given gradually to individuals who have phobia. The results show that the development of Android-based Virtual Reality applications is able to help individuals efficiently and effectively overcome Arcophobia by using simulated altitude situations. This application has 3 stages of desensitization (exposure) in a Virtual Reality environment that is made in such a way that individuals can slowly get used to their phobia. In addition, this application collects heart rate data to assess how severe the phobia experienced by the individual there are 3 objective assessments to determine how bad the phobia suffered by the user is if the user's heart rate ranges from 60bpm - 100bpm (normal) while 105bpm - 115bpm is included in the category (quite normal) and 120bpm-200bpm is categorized (bad), from these 3 assessment categories provide additional information that is useful for objectively evaluating the progress of therapy.